How to completely secure your home. - Hall, Gerald (New York Tab Books, 1978)
What can you do to protect your family and property against crime and the potential danger of life? Here are ALL the answers in straightforward, no-nonsense language. All known methods of maintaining home security and protection against crime and fire are described in laymans terms.
Keywords: Reference